Poikiloderma atrophicans vasculare as a pointer to reticulosis of the skin. Issue 597 (July 1975) - Chapman, Robert S.; Paul, C. Jose
Abstract : A case of reticulosis of the skin (mycosis fungoides) terminating in reticulum cell sarcoma is described where the features of poikiloderma atrophicans vasculare had been present for 40 years. The likelihood of reticulosis eventually developing after such a change in the skin is believed to be around 50%.